Maintaining ground support capacity to anticipate stress change episodes in Panel 0, Oyu Tolgoi mine - Batkhuu, B.; Boldbaatar, A.; Simanjuntak, K.; Ganbold, B.-E.; Bayar, E. (Deep Mining 2024: Proceedings of the 10th International Conference on Deep and High Stress Mining, 2024)
It is widely recognised that footprint reliability is one of the main indicators to have a safe and productive cave operation, especially during the cave establishment where the footprint will experience stress change episodes. During the cave establishment stage, the undercutting and drawbell construction rate is linked directly to the cave health, where maintaining its rate at the designed level will be relied on to maintain footprint stability. This paper aims to share the selected approach called the preventive support maintenance (PSM) program and its implementation result at Panel 0 (P0), the first operated block cave at Oyu Tolgoi (OT). This approach aims to maintain the rock mass pillar integrity by proactively adding new ground support elements in advance to enhance rather than exhaust the capacity of the original ground support system, which may lead to pillar instability. The robust geotechnical monitoring system established at the mine has contributed to the success of the PSM program implementation and the successful completion of Panel 0 undercutting as per plan. This approach has effectively mitigated the risks of rock mass integrity and associated personnel safety and thereby minimised disruptions to the production schedule.